Comparison of Subsoiler Plow Performance using Different Vibration Wings Designs - Al-Aabagh Hussein Alaa Aldin; Hilal Yousif Yakoub; Mahdi Karrar (Acta Technologica Agriculturae)
The study aims to manufacture and develop the vibrating wings for the subsoil plough and to evaluate the performance of the locally manufactured wings and their impact on the stability of the driver’s seat, noise, slipping, and fuel consumption. Three factors were used to evaluate the performance of the subsoiler plough, the factors including the types of vibrating wings, traditional vibrating wings (TD35) and two designs of locally manufactured wings (ND35 and ND45), and two angles of penetration of 40° and 50° at a speed of wings vibration of 60 and 120 m·s−2. The experiment was analysed using a randomised complete block design with a split-plot design and Duncan’s multiple range test at the 0.05% and 0.01% probability levels. The results showed that the stability of the driver’s seat and noise in TD35 was higher than that in both ND35 and ND45, with higher values of approximately 2.450 m·s−2 and 86.4 dB. The vibration and noise values are considered higher than those specified by international organisations that protect farmers in agricultural work (European Parliament Directive 2003/10/EC). Moreover, ND35 recorded the lowest slipping and fuel consumption results, estimated at 7.948% and 4.563 l·h−1 at the penetration angles of 50° and 40°, respectively. Finally, the results showed that the stability of the driver’s seat, noise, slipping, and fuel consumption were higher at TD35; simultaneously, the best results were achieved as the solution for the problem when using ND35 in the 40° and 50° penetration angles with both wings vibrations. The conclusion is that local vibrating wing designs reduced all the characteristics studied.